Turn It and Turn It Again Studies in the Teaching and Learning of Classical Jewish Texts - Fendrick, Susan P.; Levisohn, Jon A. (Academic Studies Press, 2013)
The study of classical Jewish texts is flourishing in day schools and adult education, synagogues and summer camps, universities and yeshivot. But serious inquiry into the practices and purposes of such study is far rarer. In this book, a diverse collection of empirical and conceptual studies illuminates particular aspects of the teaching of Bible and rabbinic literature to, and the learning of, children and adults. In addition to providing specific insights into the pedagogy of Jewish texts, these studies serve as models of what the disciplined study of pedagogy can look like. This book will be of interest to teachers of Jewish texts in all contexts, and will be particularly valuable for the professional development of Jewish educators.
Description based on print version record.
KU Open Services
Keywords: Religion / Judaism; Religion; Electronic books